KELAYAKAN POP-UP BOOK KERAGAMAN JAMUR DI HUTAN LINDUNG GUNUNG NANING PADA MATERI KEANEKARAGAMAN HAYATI - Ressi Domitila; Laili Fitri Yeni; Titin Titin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2017)
AbstractThis reseach aims to know the feasibility of pop-up book media variety of macroscopic fungi in Hutan Lindung Gunung Naning, as a learning media on biodiversity material in X SMA. This reseach consist of two step. First step is making of pop-up book media and second step is validation of pop-up book media. This reseach was quantitative with descriptive method. Pop-up book media validated by five validators, two lecture pg biology Education FKIP Untan, and there teachers of biology X SMA. One teacher from SMA/MA Negeri 1 Nanga Taman, one teacher from SMA/MA Negeri 1 Sekadau Hulu, and one teacher from SMA/MA Negeri 1 Nanga Mahap. Instrument for validation pop-up book media using validation sheet comprise of ten criteria, with analysis data using Content Validity Ratio (CVR) dan Content Validity Indeks (CVI). Based on data analysis of the validation result, pop-up book media is valid with the value of each Content Validity Ratio (CVR) from ten criteria is 1,00 with Content Validity Indeks (CVI) value is 1,00, so pop-up book media fit to use as learning media on biodiversity material.Keywords: Pop-up book Media, Feasibility, Material Biodiversity